PEMBERDAYAAN PESISIR BERBASIS PRODUK: PENINGKATAN KAPASITAS PRODUKSI DAN AKSES PASAR KERUPUK TIRAM DI DESA KUALA LANGSA - Muhammad Rizqi Zati; Dhian Rosalina; Fiddini Alham (Universitas Mataram, 2025)
Kuala Langsa Village, located along the coast of Langsa City, Aceh, possesses abundant oyster resources; however, their utilization remains limited to the sale of fresh oysters with low added value. The local community lacks knowledge and awareness in developing innovative oyster-based products with higher economic value. The objective of this program is to enhance economic independence through innovation in oyster-based product processing. The activities were designed through a participatory approach in collaboration with the PKK Kuala Bersama women's group. The stages included socialization on the importance of product diversification, technical training on oyster cracker production in accordance with food safety standards, modern packaging training, digital marketing training, and continuous mentoring and evaluation. The results of this program indicate that 16 out of 20 partner members successfully practiced oyster cracker production, including processing and packaging products with improved quality and longer shelf life. Additionally, 10 of 20 members began marketing their products through social media and online marketplaces, reaching consumers beyond their local area. This community service initiative successfully addressed the challenge of low added value in oyster resources, enabling the Kuala Langsa community to transform oysters into innovative products and strengthen the local coastal economy by developing a competitive flagship product—oyster crackers.